2014
DOI: 10.1016/j.neuron.2014.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Human Striatal Neurons by MicroRNA-Dependent Direct Conversion of Fibroblasts

Abstract: SUMMARY The promise of using reprogrammed human neurons for disease modeling and regenerative medicine relies on the ability to induce patient-derived neurons with high efficiency and subtype-specificity. We have previously shown that ectopic expression of brain-enriched microRNAs (miRNA), miR-9/9* and miR-124 (miR-9/9*-124), promoted direct conversion of human fibroblasts into neurons. Here we show that co-expression of miR-9/9*-124 with transcription factors enriched in the developing striatum, BCL11B (also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
265
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(281 citation statements)
references
References 62 publications
5
265
0
Order By: Relevance
“…In a recent study, CTIP2 was reported as the only transcription factor tested that was able to directly reprogram dermal fibroblasts into DARPP32 + neurons, suggesting that it is a potential patterning target of the activin/Smad pathway (Victor et al, 2014). Activin administration also induced the upregulation of other LGE gene markers such as NOLZ1, which marks cells leaving the cell cycle in the mantle zone (Chang et al, 2004;Urbán et al, 2010), and FOXP2, which marks cells destined for the striosomes (Takahashi et al, 2003).…”
Section: Activin Promotes An Lge Phenotypementioning
confidence: 99%
“…In a recent study, CTIP2 was reported as the only transcription factor tested that was able to directly reprogram dermal fibroblasts into DARPP32 + neurons, suggesting that it is a potential patterning target of the activin/Smad pathway (Victor et al, 2014). Activin administration also induced the upregulation of other LGE gene markers such as NOLZ1, which marks cells leaving the cell cycle in the mantle zone (Chang et al, 2004;Urbán et al, 2010), and FOXP2, which marks cells destined for the striosomes (Takahashi et al, 2003).…”
Section: Activin Promotes An Lge Phenotypementioning
confidence: 99%
“…This is a promising approach given that most converted cells retain remnants of their original cell identity Morris et al, 2014). In addition, miRNAs are likely to drive neuronal conversion by inducing changes in neuron-specific BAF chromatin remodeling complexes (Tang et al, 2013), fostering a neuronal ground state permissive for the activity of the terminal selector genes that control the batteries that drive conversion to specific neuronal subtypes (Victor et al, 2014). This parallels the induction of lineage competence via pioneer factor expression, followed by recruitment of cooperative factors to elicit changes in fate.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Indeed, this approach has been used for inducing many other neuronal subtypes lost in traumatic injury or neurodegenerative diseases, and generation of which in vitro could be potentially useful for cellbased therapies as well as for disease modelling (Blanchard et al, 2015;Caiazzo et al, 2011;Gascón et al, 2016;Rouaux and Arlotta, 2013;Son et al, 2011;Victor et al, 2014;Wainger et al, 2015). Especially for the latter, direct reprogramming has the advantage of maintaining the age of the starter cell (Mertens et al, 2015), in contrast to the re-setting that occurs when generating induced pluripotent stem cells (Lapasset et al, 2011).…”
Section: Neuronal Subtype Specification: From Dopaminergic Neurons Tomentioning
confidence: 99%
“…1A) and Bcl11B (also known as Ctip2), a late postmitotic differentiation factor from this region . Interestingly, some transplanted induced MSNs survived for more than 6 months and projected to their correct targets, the globus pallidus and substantia nigra (Victor et al, 2014). Interestingly, Ctip2 is required for the normal development of striatal patch neurons, but so far the patch identity…”
Section: Striatal Neuronsmentioning
confidence: 99%